Novel dihydroartemisinin derivative Mito-DHA5 induces apoptosis associated with mitochondrial pathway in bladder cancer cells - Linfan Xiao; Cangcang Xu; Peiyu Lin; Lingli Mu; Xiaoping Yang (BMC, 2022)
Abstract Background Bladder cancer is the second most common genitourinary malignancy and the eleventh most common cancer worldwide. Dihydroartemisinin (DHA), a first-line antimalarial drug, has been found to have potent antitumor activity. In our previous study, a novel dihydroartemisinin derivative Mito-DHA5 synthesized in our laboratory has a stronger anti-tumor activity than DHA. In this study, we investigated the apoptotic effect of Mito-DHA5 on bladder cancer T24 cells and molecular mechanisms underlying. Methods Antitumor activity in vitro was evaluated by MTT, wound healing and cloning formation assays. Mitochondrial membrane potential (MMP) was detected by JC-1 probe and ROS levels were measured by specific kit. The expression of caspase-3, cleaved-caspase3, mitochondrial Cyt-C, Bcl-2, Bax and PARP in T24 cells was evaluated by Western blotting. Results The results showed that Mito-DHA5 reduced cell viability with an IC50 value of 3.2 µM and induced T24 cell apoptosis in a dose-dependent manner, increased the production of ROS and decreased MMP. Mito-DHA5 could down-regulate the expression of Bcl-2, mitochondrial Cyt-C, Caspase-3, PARP and up-regulate the expression of Bax and cleaved Caspase-3. Conclusions These data suggested that Mito-DHA5 had a potent inhibitory effect on T24 bladder cancer cell growth and induced these cells apoptosis associated with mitochondrial pathway.